A SURVEY ON COMPACT MULTIBAND SLOTTED PLANAR MONOPOLE ANTENNA WITH BRANCH LINES FOR WIRELESS COMMUNICATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
An explosive growth of the wireless radio communication systems is currently observed in the microwave band. In the short range communications or contactless identification systems, multiband antenna has been playing a very important role for wireless service requirements. Multiband antennas may have lower-than-average gains or be physically large in comparison to single-band antennas in order to accommodate the multiple bands. The wires at the center of the feed of simple multiband antennas are separated vertically by a small amount, and the ends are separated by a few inches. These simple dimensions make it possible to cut antenna lengths for given frequencies and eliminate the need for pruning. Wireless local area network (WLAN) and Worldwide Interoperability for Microwave Access (WiMAX) have been widely applied in mobile devices such as handheld computers and intelligent phones. These two techniques have been widely considered as a costeffective, viable, and high-speed data connectivity solution, enabling user mobility. Microstrip patch antennas are popular in wireless communication, because they have some advantages due to their conformal and simple planar structure. They allow all the advantages of printed -circuit technology. There are varieties of patch structures available but the rectangular, circular and triangular shapes are most frequently used.